Il viaggio - Maxia, Michela (Milano University Press, 2022)
The book, for kids between the ages of 11 and 13, is part of an action research project (MinViTI) dedicated to the accompaniment and support of youngsters who have a family member hospitalized in Intensive Care Unit. Through the journey of a kid, led by a wise man in the world where his father is battling his illness, the reader will find a way to recognize and share his emotions, activate resources and prepare for a possible visit to the Intensive Care Unit. The book is promoted in collaboration with the Intensive project, it, a scientific initiative supported by SIAARTI, Aniarti, AAROI-EMAC, and dedicated to the humanization of ICU care.